Efectos socioeconómicos derivados de la tala de manglar en la zona Sacamano de la parroquia urbana Puerto Jelí del cantón Santa Rosa, periodo 2005-2010 - Sempértegui Serrano, Saúl Santiago (2013)
Due to the impacts of this threat, ancestral users who are engaged in collecting and catching marine species and living along the coastal edge, have been affected by increased levels of pollution and poor extraction practices. The fisheries and logging resources of this fragile ecosystem, whose impact is seen directly in the fisheries.